Ligament Healing After Anterior Cruciate Ligament Rupture: An Important New Patient Pathway? - Florian Forelli; Jérôme Riera; Jean Mazeas; Claire Coulondre; Sven Putnis; Thomas Neri; Alexandre Rambaud (International Journal of Sports Physical Therapy)
Recent studies have shown satisfactory functional results after spontaneous healing of a ruptured anterior cruciate ligament (ACL). However, current literature on this topic may exclude important parting selection, outcome measures, and long-term results. Rehabilitation protocols applied in those studies, as well as objective assessments appear far from the usual gold standard after ACL reconstruction. Ideally, outcomes measures should be based on the same testing procedures that are recommended to clear an athlete to return to sport following ACL reconstruction. There is still a lot to understand in how an injured ACL may heal, and therefore ACL injury management should be individualized to each patient and carefully discussed.